Lived Experiences and Social Transformations : Poetics, Politics and Power Relations in Practical Theology - Radford, CL Wren, (Theology in Practice ;, 2022)
Practices of sharing marginalised lived experiences are framed as providing insight into injustices; yet social inequalities influence whose experiences, and whose interpretations of these experiences, are seen as valid. Lived Experiences and Social Transformations analyses academic and activist encounters with lived experiences, arguing that these practices reinforce or disrupt power relations. Through the example of UK activists sharing their experiences of poverty, Wren Radford advocates for collaborative interventions that emphasise the critical, creative knowledges enmeshed in marginalised experiences. The book compellingly enacts this approach to practical theology; rooted in concrete issues and argued through poetic writing, artwork, and interdisciplinary sources.